High genetic variation within mitochondrial CO1 in Middle European Thanasimus formicarius (Linné, 1758) (Coleoptera: Cleridae) - Gerstmeier, Roland; Morinière, Jérôme; Hendrich, Lars (Zootaxa, 2019)
The aim of this study is to assess the species status of the Middle-European Thanasimus Latreille, 1806 species using mitochondrial CO1 sequence data. Molecular biological results clearly support the synonymy of T. pectoralis (Fuss, 1863) and T. rufipes (Brahm, 1797) with T. femoralis (Zetterstedt, 1828) as already proposed by Kolibáč (1992). Results of the present study indicate high genetic variation within T. formicarius (Linné, 1758) and emphasize the study of population dynamics of T. formicarius within Europe. Furthermore, preliminary screening of all available T. formicarius sequences on BOLD and Genbank (shorter than 500bp) indicates the presence of a “Continental” and a more “Atlantic” clade in T. formicarius. To support our hypothesis of a probably cryptic species among T. formicarius, more studies, with more specimens from different populations, especially from southern England, northern France and the northern part of the Iberian Peninsula, will be necessary.